Brain activity in different brain areas of patients with diabetic vitreous hemorrhage according to voxel-based morphometry - Li-Jun Ji; Jin-Yu Hu; Yan-Mei Zeng; Qian Ling; Jie Zou; Cheng Chen; Liang-Qi He; Xiao-Yu Wang; Hong Wei; Xu Chen; Yi-Xin Wang; Yi Shao; et al. (International Journal of Ophthalmology)
AIM: To elucidate the neuropathological mechanisms underlying diabetic vitreous hemorrhage (DVH) and its correlation with clinical characteristics. METHODS: Twenty-one individuals with DVH (male/female 12/9; mean age 52.29±11.66y) were selected, alongside 21 appropriately matched controls with diabetes mellitus (DM). Voxel-based morphometry (VBM) techniques were employed to identify aberrant functional regions in the brain. Receiver operating characteristic (ROC) curves were utilized for classification based on the average VBM values of the two groups, and Pearson correlation analysis was conducted to assess the relationship between average VBM values in distinct brain regions and clinical manifestations. RESULTS: Relative to the DM controls, DVH patients exhibited reduced VBM values in the right superior temporal pole, the right superior temporal gyrus, the right medial orbital frontal gyrus, and the left superior frontal gyrus. Furthermore, ROC curve analysis of these four brain regions in DVH patients demonstrated a high degree of accuracy, as indicated by the area under the curve. The average VBM value in each of these regions exhibited a negative correlation with both the duration of DVH and the score on the Hospital Anxiety and Depression Scale (HADS). CONCLUSION: Pathological alterations in four distinct brain regions are observed in patients with DVH, potentially reflecting neuropathological changes associated with this condition.